MENYIBAK MISTERI ALAM RAYA MELALUI AYAT-AYAT SEMESTA - Nurul Wakia; Sabriadi HR (Universitas Islam Negeri Alauddin Makassar, 2021)
Abstract This paper reveals the secrets of the universe through the verses of the universe. The data is obtained through library research. The results show that the planet Earth and humans have the ability to vary the order of the universe. In the universe, humans see the existence of various organizations of matter in the form of various luminous objects such as moons, planets, stars, nebulae, star clusters, galaxies, and galaxy clusters.This magnificent material figure of the universe, whether it is successful or not successfully captured by the human senses, is controlled by